Investor protection and market liquidity revisited. Issue 4 (3rd August 2015) - Shi, Xiaofeng; Dempsey, Michael; Duong, Huu Nhan; Kalev, Petko S.
Abstract : Purpose: – This paper aims to establish the relation between corporate governance – as represented by investor protection at both the legal and firm levels – and stock market liquidity. Design/methodology/approach: – This paper avails of the unique features of Hong Kong- and China-based stocks that are traded on the Hong Kong Stock Exchange so as to test whether differences between "common law" and "civil law" legal environments contribute to differences in stock liquidity. In addition, by constructing an internal corporate governance index score for each firm based on board size, board independence and information on the audit and remuneration committee, we document whether firms with better corporate governance scores have narrower spreads, greater depth and higher trading volumes. Findings: – Overall, results provide support for a linkage between corporate governance issues – as investor rights protection at both the environment and firm protection levels – and stock market liquidity. Research limitations/implications: – This paper recognizes that investor protection constitutes a single component of the desirability of investing in a firm's stock. Nevertheless, it does appear to constitute an important component of a stock's attractiveness. Practical implications: – The practical implications are clear, namely, that good corporate governance of firms leads to their attractiveness as investment vehicles (for both the shorter and the longer terms). Social implications: – The paper has clear social implications. In particular, the paper serves to highlight that prospects for enduring wealth creation are contingent on the safeguards accorded to the equity ownership of a firm's stock. Originality/value: – The originality lies in taking advantage of the unique features of the Chinese and Hong Kong firms on the Hong Kong Exchange, so as to examine the contrasting influences of common law and civil law on stock liquidity. Thus, the authors allow for the effects of corporate governance across the two legal environments (China and Hong Kong) to be compared and contrasted while maintaining other influences unchanged across Chinese and Hong Kong shares.